EFFECT OF LACTATION PERIOD ON THE CHEMICAL AND FATTY ACIDS COMPOSITION OF BREAST MILK IN MOSUL CITY - Abdullah M. Thannoun (Mesopotamia Journal of Agriculture)
The effect of Lactation period (Infant age) on the chemical and fatty acids composition of breast milk including colostrum in Mosul city was studied. Three hundred and eighty nine normal samples of human (breast) milk of healthy lactating mothers of 17 to 46 years of age nurturing infants starting from the birthday (1st day of infants age for colostrum) until 2.5 years of age were collected from five area in Mosul city and Al-khansaa delivery hospital. Thirty of the above subjects were chosen as volunteers to give constant periodically and monthly breast milk samples for fatty acid analysis. Results show that there was an effect of lactation period on the fat, protein, lactose and ash % of the breast milk. Fat and lactose % were increased, whereas, protein and ash % decreased with lactation period. Generally, there was no significant (P<0.05) effect of lactation period on the Saturated fatty acid (SFA) and Polyunsaturated fatty acid (PUFA) although, there was slight increased in both SFA and PUFA % with lactation period. PUFA/SFA ratio was also not affected. It was concluded that the components such as fat, protein and lactose of human milk might be influenced by lactation period.